2007
DOI: 10.1186/1471-2490-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of complications of male circumcision in Anglophone Africa: a systematic review

Abstract: BackgroundThere is growing evidence that male circumcision (MC) prevents heterosexual acquisition of HIV by males in sub-Saharan Africa, the region of the world heavily affected by the HIV pandemic. While there is growing support for wide-spread availability and accessibility of MC in Africa, there is limited discussion about the prevalence of physical complications of male circumcision on the continent.MethodsA systematic literature search and review of articles in indexed journals and conference abstracts wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 30 publications
0
41
3
4
Order By: Relevance
“…Most of this literature is about surgery undertaken in the developed world; there are far fewer data on medical circumcision in the developing world or traditional circumcision practices. 36 Beyond individual effects and consequent effects on partners and over the life course, there may be longer-term social impact, e.g. community expectations and understandings over time may change and affect compliance and participation in circumcision.…”
Section: Putting Male Circumcision In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this literature is about surgery undertaken in the developed world; there are far fewer data on medical circumcision in the developing world or traditional circumcision practices. 36 Beyond individual effects and consequent effects on partners and over the life course, there may be longer-term social impact, e.g. community expectations and understandings over time may change and affect compliance and participation in circumcision.…”
Section: Putting Male Circumcision In Contextmentioning
confidence: 99%
“…UNAIDS is clearly aware of these issues, 1 but there is not yet sufficient evidence on the extent of safety problems or the social complexity of traditional circumcision across sub-Saharan Africa (or elsewhere in the developing world for that matter), or on the level of adverse effects currently experienced, 44,36 and how these might be addressed at policy and programme level. There were programme successes reported in abstracts at the Toronto conference, 45 but these barely scratch the surface of what might be needed to go to scale on significantly improving safety in traditional circumcision.…”
Section: Other Contextual Issuesmentioning
confidence: 99%
“…[3][4][5] In these studies, complications following male circumcision ranged from 1.7% to 7.6% and were mostly of minor clinical significance. 6,7 However, serious complications and even deaths have been reported from traditional male circumcision carried out on adolescents. 8,9 While medical male circumcision is increasingly being incorporated in comprehensive strategies for the prevention of HIV infection 10 , traditional providers will continue to be an important source of circumcision for many males in eastern and southern Africa and will not easily be replaced by male circumcision performed in a clinical setting for reasons that are both cultural and linked to health service capacity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Before the RCTs, outcomes in Africa for male circumcision among adults were poorly documented. In a review, 6 adverse event rates following African male circumcisions ranged from 0 to 24%. The RCTs, which provided services in a clinical trial setting, reported the following adverse event rates: 3.8% in Orange Farm, South Africa; 1.5% in Kisumu, Kenya; and 3.6% in Rakai, Uganda.…”
Section: Introductionmentioning
confidence: 99%